The Impact of Macroeconomic Uncertainty on Cash Holdings for Non-Financial Firms - Oleksandr Talavera; Neslihan Ozkan; Mustafa Caglayan; Christopher F. Baum (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper investigates the effects of macroeconomic volatility on non-financial firms' cash holding behavior. Using an augmented cash buffer-stock model, we demonstrate that an increase in macroeconomic volatility will cause the cross-sectional distribution of firms' cash-to-asset ratios to narrow. We test this prediction on a panel of non-financial firms drawn from the annual COMPUSTAT database covering the period 1957-2000, and find that as macroeconomic uncertainty increases, firms behave more homogeneously. Our results are shown to be robust to the inclusion of the levels of several macroeconomic factors.
Keywords: 330; Cash holdings; macroeconomic uncertainty; time series; ARCH; non-financial firms; Liquide Mittel; Betriebliche Liquidität; Makroökonomischer Einfluss; Volatilität; Konjunktur; Schätzung; Vereinigte Staaten